2003
DOI: 10.1074/jbc.m212296200
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB Specifically Activates BMP-2 Gene Expression in Growth Plate Chondrocytes in Vivo and in a Chondrocyte Cell Line in Vitro

Abstract: In long bones, morphogenesis is followed by an extended period of growth. Longitudinal growth occurs at the growth plate by endochondral ossification, a process in which cartilage is formed and then remodeled into bone (1, 2). The multistep process of chondrogenesis involves: 1) the aggregation of mesenchymal cells into prechondrogenic condensations, 2) differentiation of the condensed prechondrogenic mesenchyme into small immature chondrocytes, and 3) chondrocyte maturation followed by ossification, starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 22 publications
4
102
1
1
Order By: Relevance
“…Further, NF-B has been reported to activate BMP-2 expression in osteoblasts as well as in chondrocytes (36). We found that oxLDL induces rapid and sustained NF-B phosphorylation in human CAECs, and inhibition of NF-B reduces BMP-2 expression.…”
Section: Discussionmentioning
confidence: 56%
“…Further, NF-B has been reported to activate BMP-2 expression in osteoblasts as well as in chondrocytes (36). We found that oxLDL induces rapid and sustained NF-B phosphorylation in human CAECs, and inhibition of NF-B reduces BMP-2 expression.…”
Section: Discussionmentioning
confidence: 56%
“…Indeed, NF-〉 binding sites appear to be present in the promoter region of the rat BMP-2 gene, and a recent study reported that NF-〉 binds an NF-〉 response element in the 5Ј flanking region of the BMP-2 gene in mouse chondrocytes. 26 Interestingly, we found that this NF-〉 binding site is located in an evolutionary, highly conserved region of the BMP-2 promoter ( Figure 1C), which provides an explanation for the similar upregulation of BMP-2 expression in human and rat endothelial cells by TNF-␣ ( Figures 1A and 1D). The in vivo significance of the regulation of vascular BMP-2 expression by TNF-␣ and NF-〉 is supported by the lower level of BMP-2 expression in vessels of TNF-␣-deficient mice ( Figure 1G).…”
Section: Discussionmentioning
confidence: 78%
“…Although the reasons for the accelerated chondrocyte hypertrophy are not fully clarified, NF‐κB signalling has been found to be involved in it 43. NF‐κB pathway could inhibit the chondrogenic differentiation of mesenchymal cells by down‐regulating SOX9 44.…”
Section: Discussionmentioning
confidence: 99%